Web-Based Media Using a Project-Based Learning Approach in Textile Materials for Children’s Clothing - Erni; Yudhistira Anggraini; Halimul Bahri; Nurhayati Tanjung; Nikmat Akmal (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop web-based learning media using a Project-Based Learning approach on textile materials for children's clothing and to determine its feasibility and students’ responses in supporting quality education. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The implementation stage involved students of the Fashion Education Study Program. Data were collected through expert validation sheets and student response questionnaires using a Likert scale. The results showed that the developed media were categorized as very valid, with a material expert validation score of 94.3% and a media expert validation score of 92.5%. Students’ responses also indicated very positive results, with an average score of 92.5%. These findings demonstrate that the web-based learning media integrated with the Project-Based Learning approach are feasible and effective in supporting students’ engagement and understanding of textile materials for children's clothing. Therefore, this media can be used as an alternative instructional tool to improve the quality of learning in vocational fashion education.